A structural decomposition of global raw material consumption - Frank Pothen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
Between 1995 and 2008, the global extraction of biomass, fossil fuels, and minerals grew from 48 to 69 billion metric tons. This study investigates how changing consumption and investment patterns affected the aforementioned increase. A series of Structural Decomposition Analyses at a global level as well as for 38 major economies is conducted. The analyses disentangle the drivers of Raw Material Consumption, which measures the extraction of materials necessary to produce a country's final demand. Data is taken from the World Input-Output Database. The results suggest that rising final demand is the predominant driver of growing Raw Material Consumption. Furthermore, final demand shifted into countries that consume material intensive goods. This shift was particularly pronounced for construction minerals and investment, indicating that infrastructure investment in industrialising nations was a key driver. The mix of goods in final demand slightly dematerialised. Falling material intensities in extractive industries as well as changes in production and trade patterns decelerated the growth of Raw Material Consumption. The country-level Structural Decomposition Analyses obtained qualitatively similar results.
urn:nbn:de:bsz:180-madoc-394013
Keywords: Q2; Q3; C67; 330; Raw Material Consumption; Structural Decomposition Analysis; Input-Output Models